CTCF Mediates Replicative Senescence Through POLD1 - Hou, Yuli; Song, Qiao; Gao, Shichao; Zhang, Xiaomin; Wang, Yaqi; Liu, Jing; Fu, Jingxuan; Cao, Min; Wang, Peichang (Frontiers in Cell and Developmental Biology, 2021)
POLD1, the catalytic subunit of DNA polymerase δ, plays a critical role in DNA synthesis and DNA repair processes. Moreover, POLD1 is downregulated in replicative senescence to mediate aging. In any case, the components of age-related downregulation of POLD1 expression have not been fully explained. In this article, we elucidate the mechanism of the regulation of POLD1 at the transcription level and found that the transcription factor CTCF was bound to the POLD1 promoter area in two sites. The binding level of CTCF for the POLD1 promoter appeared to be related with aging and was confirmed to be positively controlled by the CTCF level. Additionally, cell senescence characteristics were detected within the cells transfected with short hairpin RNA (shRNA)-CTCF, pLenti-CMV-CTCF, shRNA-POLD1, and pLenti-CMV-POLD1, and the results showed that the CTCF may contribute to the altered expression of POLD1 in aging. In conclusion, the binding level of CTCF for the POLD1 promoter intervened by an age-related decrease in CTCF and downregulated the POLD1 expression in aging. Moreover, the decrease in CTCF-mediated POLD1 transcription accelerates the progression of cell aging.